MENGEMBANGKAN PENDIDIKAN KARAKTER CALON GURU SEJARAH MELALUI LESSON STUDY - Bobi Hidayat (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The mastering of character building for teaching learning history must be applied since the history teacher were learning in university. One of the mode that can be used is applying lesson study model in learning process whether in micro teaching or when the history students get teaching practice in school. There are three things that includes in teaching learning uses lesson study model, there are: plan, do, observation and see. Lesson study model is opened teaching learning process. Through good lesson study design, the history teacher candidate can be trained in having good teaher character building such as honest, discipline, care to other people, confidence, creative, overt and patient.